ADAPTASI PEGAWAI DINAS SOSIAL PROVINSI RIAU DALAM PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI MASA PANDEMI COVID – 19 TAHUN 2020 - Adhe Fadhila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of the Work From Home (WFH) policy, which requires state civil servants to work remotely/from home, is one of the strategies given by the government in anticipating the spread of Covid-19 in all levels of government, including the Riau Province Social Service. The study uses a theoretical study of 4 (four) COBIT Domain functions according to (Indrajit, 2014). The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Pekanbaru City, precisely at the Social Service of Riau Province. The types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to research. The problem in this study is that the adaptation of the Riau Provincial Social Service employees in the use of technology, information and communication during the COVID – 19 pandemic in 2020 is not optimal due to several determinants of the success of employee adaptation. The purpose of this study was to find out how the adaptation of Provincial Social Service employees in the use of information and communication technology during the covid-19 pandemic. The results of the study were that the adaptation of Riau Province Social Service employees in the use of technology, information and communication during the COVID-19 pandemic in 2020 went well. , although there are still some obstacles. Ability and skill factors are the main factors inhibiting Keywords: Adaptation, Employees, ICT, Covid – 19